PEMIKIRAN IBNU SINA TENTANG PENDIDIKAN DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM KONTEMPORER - Yuli, Yunita; Izhar Musyafa (TAUJIH: Jurnal Pendidikan Islam, 2023)
Islamic education theory today cannot be separated from the theories developed by philosophers, scholars and previous Islamic figures. One of the figures who made an important contribution to Islamic education was Ibn Sina. The aim of this research is to investigate Ibn Sina's educational ideas and their application to contemporary Islamic education. This type of research is library research using secondary sources in the form of books and scientific journals and documentation study data collection methods and using content analysis data analysis methods. The findings of this research show that Ibn Sina's thoughts about the concept of education include educational goals, curriculum, methods and educational concepts. Ibn Sina's thoughts on education have relevance to contemporary Islamic education.